Development of MGDA Software for Calculation of Patient Specific Mean Glandular Dose during Mammography - Nahar, Meherun; Sazzad, M; Mollah, Abdus Sattar; Mohammad Akramuzzaman, Mir (Bangladesh Journal of Nuclear Medicine, 2018)
Abstract not available Bangladesh J. Nuclear Med. 18(2): 156-160, July 2015